2007
DOI: 10.1590/s1413-70542007000500033
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação nutricional de rações comerciais e semente de girassol para papagaios-verdadeiros (Amazona aestiva)

Abstract: RESUMONeste experimento utilizou-se de 12 papagaios adultos, distribuídos em blocos ao acaso em seis tratamentos (T1-Ração extrusada para psitacídeos -A, T2 -Ração peletizada para psitacídeos B, T3 -Ração extrusada para psitacídeos C, T4 -Ração para cães linha prêmio; T5-Ração para cães linha econômica e T6 -Semente de Girassol), durante três períodos de colheita, totalizando seis repetições por tratamento. Avaliaram-se os valores de energia metabolizável aparente e verdadeira (EMA e EMV) e corrigidas pelo nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
3
5
0
Order By: Relevance
“…Saad et al. () evaluated for Blue‐fronted parrots two types of extruded foods and one type of pelleted food, verifying even greater amounts of waste than were observed in the present study; they observed losses of 40–74%. Due to the influence of the food format and size on its manipulation and consumption by macaws, we sought to produce foods with similar formats and size.…”
Section: Discussionsupporting
confidence: 78%
“…Saad et al. () evaluated for Blue‐fronted parrots two types of extruded foods and one type of pelleted food, verifying even greater amounts of waste than were observed in the present study; they observed losses of 40–74%. Due to the influence of the food format and size on its manipulation and consumption by macaws, we sought to produce foods with similar formats and size.…”
Section: Discussionsupporting
confidence: 78%
“…Sunflower seed provides higher fat and lower starch intake, which may at least partially explain the respectively higher and lower apparent digestibility of these nutrients compared to those verified for prepared feeds (Sibbald, ). Comparing the three prepared feeds, the digestibility values were compatible with previous data on African grey parrots (Kalmar et al, ), blue‐fronted parrots (Saad, Ferreira, Borges, et al, ) and blue‐and‐gold macaws (Veloso et al, ). Fat and starch digestibility were lower, respectively, for EXT H and EXT L feeds compared with the PEL diet.…”
Section: Discussionsupporting
confidence: 88%
“…Sunflower seed kernels have shown to be highly digestible for parrots (Saad, Ferreira, Borges, & Lara, 2007). However, a direct comparison between sunflower seed kernel and prepared diet digestibility is difficult due to their many differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in captivity, diets are normally elaborated empirically, according to the choices and habits observed in wild animals, by trial and error and taking into account the body condition of each animal. Nevertheless, such factors may not be sufficient to attend the individual nutritional demands (Saad et al 2007, Clauss et al 2010.…”
Section: Introductionmentioning
confidence: 99%